2012
DOI: 10.1084/jem.20110996
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya virus–induced autophagy delays caspase-dependent cell death

Abstract: Chikungunya virus induces autophagy by triggering ER and oxidative stress, and this autophagy restricts apoptosis and viral propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
146
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 74 publications
12
146
0
Order By: Relevance
“…These data indicate that the ability of hNDP52 to bind both hLC3-C and nsP2 is implicated in its species-specific proviral effect on CHIKV. These results reconcile the two apparently conflicting reports, which showed that autophagy plays an antiviral role in mouse cells [27] but a proviral role in human cells [28]. Moreover, these results suggest that the lower permissiveness to CHIKV of the mouse relative to humans [29] might result, at least in part, from the absence of the proviral role of NDP52 in the mouse.…”
Section: Ndp52-nsp2 Interaction Is Species Specificsupporting
confidence: 84%
See 2 more Smart Citations
“…These data indicate that the ability of hNDP52 to bind both hLC3-C and nsP2 is implicated in its species-specific proviral effect on CHIKV. These results reconcile the two apparently conflicting reports, which showed that autophagy plays an antiviral role in mouse cells [27] but a proviral role in human cells [28]. Moreover, these results suggest that the lower permissiveness to CHIKV of the mouse relative to humans [29] might result, at least in part, from the absence of the proviral role of NDP52 in the mouse.…”
Section: Ndp52-nsp2 Interaction Is Species Specificsupporting
confidence: 84%
“…Autophagy plays an antiviral role in CHIKV-infected mouse cells [27] and a proviral role in CHIKV-infected human cells [28]. To better understand these apparently conflicting results, we investigated the role of mouse NDP52 (mNDP52).…”
Section: Ndp52-nsp2 Interaction Is Species Specificmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Autophagy is a lysosome-dependent bulk degradation pathway, which controls the clearance and recycling of cytoplasmic components for the maintenance of cellular survival. 2 Autophagy includes at least 3 pathways: macroautophagy, microautophagy, and chaperone-mediated autophagy. 2 Of these, macroautophagy is the most prevalent form of autophagy and has been implicated in cardiovascular diseases.…”
mentioning
confidence: 99%
“…2 Autophagy includes at least 3 pathways: macroautophagy, microautophagy, and chaperone-mediated autophagy. 2 Of these, macroautophagy is the most prevalent form of autophagy and has been implicated in cardiovascular diseases. 3 In the present study, macroautophagy will be referred to as autophagy.…”
mentioning
confidence: 99%